2012
DOI: 10.5811/westjem.2011.9.6864
|View full text |Cite
|
Sign up to set email alerts
|

Verbal De-escalation of the Agitated Patient: Consensus Statement of the American Association for Emergency Psychiatry Project BETA De-escalation Workgroup

Abstract: Agitation is an acute behavioral emergency requiring immediate intervention. Traditional methods of treating agitated patients, ie, routine restraints and involuntary medication, have been replaced with a much greater emphasis on a noncoercive approach. Experienced practitioners have found that if such interventions are undertaken with genuine commitment, successful outcomes can occur far more often than previously thought possible. In the new paradigm, a 3-step approach is used. First, the patient is verbally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
273
0
42

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(318 citation statements)
references
References 21 publications
3
273
0
42
Order By: Relevance
“…Aggressive episodes develop over five phases (trigger, escalation, crisis, plateau and post crisis depression phase) (23). Detecting aggression, intervening and de-escalating at an early stage are essential (24). Regular aggression management (AM) training aims to increase staff knowledge and foster interactional competencies, such as preventing and de-escalating PVA verbally and non-verbally in a non-coercive, collaborative, and interactional approach (25).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive episodes develop over five phases (trigger, escalation, crisis, plateau and post crisis depression phase) (23). Detecting aggression, intervening and de-escalating at an early stage are essential (24). Regular aggression management (AM) training aims to increase staff knowledge and foster interactional competencies, such as preventing and de-escalating PVA verbally and non-verbally in a non-coercive, collaborative, and interactional approach (25).…”
Section: Introductionmentioning
confidence: 99%
“…113 -116 Although consensus is that verbal restraint is preferable to chemical or physical restraint, 117 reviews of the literature find primarily case studies, with a paucity of rigorous studies of verbal restraint, and little on specific strategies or efficacy. 113,118 For example, although a study by Jonikas et al found a decrease in restraint use, it was not clear whether the decrease was attributable to staff training in de-escalation techniques or to crisis intervention training, which occurred at the same time. 119 Other protocols emphasize the importance of prevention in behavior management protocols.…”
Section: Verbal Restraintmentioning
confidence: 95%
“…112 Four guiding principles for working with agitated patients are as follows: (1) maximizing the safety of the patient and treating staff; (2) assisting the patient in managing his or her emotions and maintaining or regaining control of his or her behavior; (3) using the least restrictive, age-appropriate methods of restraint possible; and (4) minimizing coercive interventions that may exacerbate agitation. 113 …”
Section: Restraint Of the Agitated Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of ED-based agitation are numerous, ranging from psychosis to intoxication (2)(3)(4)(5)8). Although verbal de-escalation is recommended as first-line treatment, in some cases this can be ineffective and medication administration may be required to prevent these patients from harming themselves or others (10,12). However, many of these medications have a relatively slow onset, require empiric dosing, and often require additional medication for calming (10,13).…”
Section: Introductionmentioning
confidence: 99%